Toxicological properties of plant-based disinfectants - A. M. Khyl; S. B. Peredera (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The article presents the results of research on the toxicity determination of phytopreparations in the composition of common powdery mildew + calamus + pear Late November + bischofite; common powdery mildew + calamus + bischofite; pear Late November + bischofite, which have a universally broad spectrum of bactericidal action against Staphylococcus aureus and Escherichia coli. When studying the toxicity of phytopreparations on guppy fish, it was found that when adding the infusion to water in the composition of common powdery mildew + calamus + pear Late November + bischofite with exposures of 30 minutes and 60 minutes, all fish in a group of 10 had an adverse reaction. With an exposure of 24 hours, mortality reached up to 20 %. The highest fish mortality occurred at 24 hours in the composition of common powdery mildew + calamus + bischofite, with a mortality rate of 40 %. The composition of pear in late November + bischofite showed no signs of toxicity; all fish in the group remained alive during the study. Visually, motor activity, behavioral reactions, changes in skin pigmentation, and breathing intensity were average. The survey of skin-irritating effects of phytopreparations was conducted on laboratory animals in 20 individuals – Alaska breed rabbits. It was established that during the observation period, the following signs were absent: the presence of temperature; moderately expressed, expressed, and sharply expressed erythema; pain (with a slight thickening of the skin followed by flaking); pain, swelling, and ulcers (thickening of the skin in the application area on the rabbit). After applying phytopreparations to the skin of rabbits with exposures of 1 hour, 24 hours, 48 hours, and 72 hours, no behavioral and visual changes of an inflammatory nature were detected. When applied to the animal's skin, the investigated plant-based disinfectants do not cause irritating, necrotic, or absorptive effects. Throughout the observation period, no visible changes were observed in laboratory animals' experimental and control groups. The conducted research indicates the possibility of safe application of these plant-based disinfectants in the presence of animals.